Становление космической цивилизации Земли: начальный период формирования системы управления. The Formation of a Spacefaring Civilization of the Earth: the Formative of a Stages of the System of Governance - Ударцев, С.Ф. (Научное наследие и развитие идей К.Э. Циолковского. Материалы 54-х Научных чтений памяти К.Э. Циолковского. Часть 2. Калуга: Изд-во АКФ «Политон», 2019)
Космическая цивилизация Земли рассматривается как вершина эволюции человечества и его земных сообществ. Выделены основные черты, особенности и задачи сложной и многоаспектной организационной структуры и системы управления периода формирования космической цивилизации Земли. Формирующиеся космические государства – главные элементы глобальной системы управления космической цивилизации Земли. Представлены возможные сценарии эволюции, основные выводы. The space civilization of the Earth is considered as the pinnacle of the evolution of humanity and the earth communities. The major features, peculiarities, and objectives of the complex and multidimensional organizational structure and system of governance during the formative stage of the space civilization of the Earth have been highlighted. The emerging space states are core components of the global system of governance of the space civilization of the Earth at a new stage of the evolution of the humanity. Possible scenarios of the evolution and key findings were presented.
Keywords: космическая цивилизация, космическое государство, человечество, сценарии эволюции, глобальное управление, система; the space civilization, the space state, humanity, scenarios of evolution, the global management, system